Lithospheric structure of the Tien Shan region constrained by joint inversion of receiver function and Rayleigh wave dispersion. (3rd April 2019) - Li, Mengkui; Lin, Xu; Wu, Tengfei; Hua, Yujin
Abstract: We obtain a lithospheric shear‐wave velocity model across the Tien Shan orogenic belt by jointly inverting Rayleigh wave group velocities and teleseismic P‐wave receiver functions at 61 broadband seismic stations deployed in this region. Our new model reveals prominent lateral variations of shear‐wave velocity in both the crust and uppermost mantle. This model reveals different structures in the upper and middle crust across the Talas Fergana Fault, which may suggest the presence of a tectonic boundary between the western and central Tien Shan beneath the fault. According to the velocity images, the depth extent of the fault is ~40 km and this is confined to the crust. Pronounced low‐velocity anomalies are imaged in the middle crust and uppermost mantle beneath the southern and middle Tien Shan, implying that the upwelling of the materials from the upper mantle could have played an important role in the mountain building.